Conductividad iónica en nuevos compositos (PEO)10(CF3COONa)-X% Al2O3 - Jurado Meneses, Nori Magali; Universidad del Tolima (2013)
To increase the ionic conductivity of solid polymer electrolyte, (PEO)10 CF3 COONa, we formed new composites by adding alumina particles as a filler. We prepared these composites by dissolving them in a liquid solvent, and characterized them through impedance spectroscopy (IS), using a Pt/electrolyte/Pt electrode configuration. The combination of polyethylene oxide (PEO) with sodium trifluoroacetate (CF3COONa) produced a reduction in resistance of up to two orders of magnitude in Nyquist plots, and up to three orders of magnitude when we added Al2O3 particles at room  temperature. DC conductivity concentration graphs show an increase in the ionic conductivity with low alumina concentrations. The new synthesized ionic conductor composite presented conductivity values of 2.00x10-5 Scm1 at room temperature and of 7.70x10-4 Scm-1 at a temperature of 383 K. Two sections of the conductivity diagrams also evidenced a temperature induced Arrhenius behavior, indicating a thermally activated process. Higher concentrations of Al2O3 induced a Vogel-Tamman-Fulcher (VTF) behavior. Conductivity variations produced by Al2O3 concentration are linked to the number of sites involved in ion transport between Al2O3 ionic electrolyte species through Lewis acid-base interactions